Effect of Salinity on Mineral Nutrient Distribution Along Growing Seedlings of Bruguiera conjugata Lamk. - A.Venkatesan, S. Sridevi, (Journal of Phytology, 2009)
Bruguiera conjugata (Rhizophoraceae) is a salt tolerant plant species which is widely distributed in Inland and coastal salt marshes area. This study reports the effect of salinity (0, 200, 400, 600 and 800 mM) on the growth and ionic content. Fresh and dry weight of plants increased with an increase in salinity. The optimal growth of B. conjugata plants were recorded at 400 mM NaCl and the growth declined with further increase in salinity. The leaf, stem and root had Ca2+, P, Mg2+, Nitrogen and micronutrients such as Fe2+, Cu2+, Zn2+ and Mn2+ content increased upto the optimum level and thereafter decreased gradually. In Na+, K+ and Cl- content increased upto optimal level of 800 mM.